Parameters of Compressive Strength of PCC Consequence Concrete the Difference in Curing Time and Specimen Shape - Syahrul Sariman; Arman Setiawan; Ridwan Ridwan (Postgraduate, University of Mataram, 2023)
The strength of concrete is determined by its compressive strength. SNI 2847-2013 has determined that the compressive strength of concrete is obtained by using a cylindrical specimen with a diameter of 15 and a height of 30 cm (C.15) or a diameter of 10 cm and a height of 20 cm (C.10) at 28 days of age. The problem commonly encountered in the field is how to estimate the acceptable compressive strength of concrete if it has not reached the age of 28 days and with specimens that do not meet the standards set out in SNI. This study aims to obtain a correction factor for the age and shape of the test object when using a cube measuring 15x15x15 cm (K.15) and not yet reaching the age of 28 days using Portland Composite Cement (PCC). Concrete is cast using 4 forms of mold namely K15, K20, C10, and C15. Then cured until the age of 7, 14, and 28 days. At each immersion age, the compressive strength of the concrete was tested for each of the 3 specimens. The results showed that the average age factor was 0.59, 0.81, and 1 at 7, 14, and 28 days of age. While the form factor of the test object against the standard K15 form shows a value of 0.950 for K20, 1.028 for C10, and 0.813 for the C15 test object